The economy of exclusion: Papa Francisco and its perspective on capitalism (Research, Society and Development, 2021)
The article analyzes Pope Francis' critique of capitalism. The constitutional principle of solidarity links the social and economic orders in democratic states governed by the rule of law faces difficulties of application due to the limited financial resources in the states. After the crisis of 2007-2008, many states launched an austerity program for social rights. At the same time, sectors such as banks made twice as much profit as in the decade before the crisis, as was the case with JPMorgan (between 2008 and 2018 it made US$ 200 billion). This context drove contemporary capitalism into the limits of mistrust, leading Pope Francis to conceptualize it as an "economy of exclusion and inequality". The text focuses on the Pontiff's critique of ideal and real capitalism and proposes its refunding based on humanist values. After all, what does Francis' capitalism refer to and what proposal should it articulate in the light of his magisterium of solidarity economy? The methodology is interdisciplinary, articulates law and economics, inductive-deductive nature, bibliographic, documentary and qualitative research. The results obtained lead us to conclude that Francis does not propose an alternative economic regime but offers foundations to reconcile economic growth with human development and to implement the social rights present in the constitutionalism of the 20th century.